(untitled) (Global Media Journal - German Edition, 2023)
International efforts aimed at developing a specific region’s or country’s media sector commonly involve both onsite actors (usually from the Global South) and external actors (usually from the Global North). Dependency theory suggests that onsite actors are (stuck) in a relationship with development agencies and donors in which “Western” notions of journalistic ethics, communication and democracy are imposed on them – and not necessarily to their advantage. Bureaucratic imperatives and institutional dynamics especially within funding agencies have been identified as strong determinants of media development practice. Yet, recent empirical insights point to local actors’ ability to assert their own strategies in the face of donor power which can be interpreted as agency. Therefore, this paper suggests making use of structuration theory to get a clearer picture of how onsite actors enact international media development practice. Structuration theory acts on the assumption that social practice is produced and reproduced as part of a dynamic interplay between agency and structure. Applied to media development practice, it allows for the analysis of the intentions and motivations of the agents involved, the conscious or subconscious rules they act upon and also the allocative and authoritative resources at their disposal. Against this background, this contribution presents the methodological design and preliminary results of a qualitative interview study on how onsite actors in the target countries of international media development perceive and negotiate their scope of action. Online interviews were conducted with participants from various world regions such as Middle East, South Asia as well as South-East Asia. The results suggest that the cultivation of long-term relationships and a diversification of international partners allow onsite actors to strengthen their agency within international media development.